Analisis Faktor Penyebab Perilaku Penyalahgunaan Narkoba Ditinjau dari Perspektif Islam dan Kesehatan Masyarakat: Literatur review - Faiz, Jihan Fadilah; Alkaff, Raihana Nadra; Muntahaya, Fika; Wiza, Siti Salmah; Gunawan, Dio; Fauziah, Amelia Lutfi; Ramadhani, Asri; Rohmah, Khofifah (Journal of Religion and Public Health, 2023)
AbstractDrug abuse is a public health problem that still occurs in Indonesia. This problem is not limited to certain age groups. Starting from the adult age group, adolescence to the age group of children who know and use drugs. This paper aims to analyze the factors that cause drug’s abuse behavior using Precede-Proceed theory approach from an Islamic and public health perspective. This study is a narrative literature review using the keywords "Drugs", "Islamic perspective", "Drug prevention" and "Impact" "Precede-Proceed theory" through the Google Scholar search engine with search ranges from 2012 to 2019. The results of this study, 10,620 journals were founded and there were 18 journals which identified as relevant to the study. There are various factors that influence drugs abuse behavior such as social factors, epidemiological factors, behavioral and environmental factors, educational and ecological factors, as well as policy and political factors. This research supports the need to instill religious values in children from an early age and the need to re-assess the policy of drug’s abuse policy makers.Keywords: Drugs Abuse, Islamic perspective, Precede-Proceed theory